Improving methods of primary prevention of STIs and HIV infection among young people - Alexey A. Khryanin; Maria V. Russkikh (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. The article considers the possibility of raising awareness among young people about STIs and HIV infection. It presents the development of the mobile application Personal Sexual Health, which includes the following sections: Sexual Infections, Protect Yourself, Frequently Asked Questions, Get help and etc. Aim. Improving methods of primary prevention of STIs and HIV infection among young people using a mobile app. Materials and Methods. The mobile application (Personal Sexual Health) was developed taking into account previously conducted scientific (sociological) research on the level of awareness of STIs and HIV infection among young people in Novosibirsk. The development of the mobile application was carried out using Agile (agile software development) methodology. Results. It was found that young people trust online information and view the Internet as a reliable source of sexual health advice. In fact, the Internet is a useful tool for spreading the reliable information about sexual health and different events detecteded to prevention of STIs and HIV-infection. The concept of the mobile application Personal Sexual Health implies raising the awareness of young people on the prevention of STIs and HIV infection. The informational component of the mobile application Personal Sexual Health was developed taking into account the previously obtained results from a sociological survey of young people. Conclusion. The modern generation of young people is forming a new ethics of communication, and the Internet is a basic source of information about sexual health for most teens and young adults. However, the information from Internet is not always correct or sufficient. Using modern, relevant, and still gaining in popularity technology (mobile apps and social media) will help to better absorb information about STIs and HIV prevention programms among young people. Personal Sexual Health is the first mobile application in Russia dedicated to sexual health and primary prevention programms of STIs and HIV-infection among young people. Background. The article considers the possibility of raising awareness among young people about STIs and HIV infection. It presents the development of the mobile application Personal Sexual Health, which includes the following sections: Sexual Infections, Protect Yourself, Frequently Asked Questions, Get help and etc. Aim. Improving methods of primary prevention of STIs and HIV infection among young people using a mobile app. Materials and Methods. The mobile application (Personal Sexual Health) was developed taking into account previously conducted scientific (sociological) research on the level of awareness of STIs and HIV infection among young people in Novosibirsk. The development of the mobile application was carried out using Agile (agile software development) methodology. Results. It was found that young people trust online information and view the Internet as a reliable source of sexual health advice. In fact, the Internet is a useful tool for spreading the reliable information about sexual health and different events detecteded to prevention of STIs and HIV-infection. The concept of the mobile application Personal Sexual Health implies raising the awareness of young people on the prevention of STIs and HIV infection. The informational component of the mobile application Personal Sexual Health was developed taking into account the previously obtained results from a sociological survey of young people. Conclusion. The modern generation of young people is forming a new ethics of communication, and the Internet is a basic source of information about sexual health for most teens and young adults. However, the information from Internet is not always correct or sufficient. Using modern, relevant, and still gaining in popularity technology (mobile apps and social media) will help to better absorb information about STIs and HIV prevention programms among young people. Personal Sexual Health is the first mobile application in Russia dedicated to sexual health and primary prevention programms of STIs and HIV-infection among young people.